"Pure" motor hemiplegia. Issue 9 (September 1975) - Chokroverty, S; Rubino, F A
Abstract : Attenuation of cerebral evoked responses after stimulation of the median nerve in the hemiplegic limbs suggested that an apparently pure motor hemiplegia in some patients may not have pure involvement of the corticospinal system. Frontoparietal metastasis, infarction in basis pontis and medullary pyramid, and occlusion of internal carotid artery in the neck resulted in pure motor hemiplegia in some individuals.